Development of methods and the study of microbiological purity of the gel of a complex dense extract of hypericum herbs and calendula flowers - T. A. Shostak; N. V. Dilay (The State Expert Center of the Ministry of Health of Ukraine, 2020)
In pharmaceutical industry antimicrobial preservatives that restrict multiplication of microorganisms and decrease bioburden are usually added in composition of hydrophilic medicines that include components of natural origin to prevent possible risks of functional changes in drugs characteristics caused by microbial contamination. Therefore, microbiological purity (MBP) is a crucial criteria for medicines quality. The purpose of the work was to develop the MBP testing methodology for complex gel containing dense extract of hypericum herbs and calendula flowers using structural-mechanical and technological studies. Methodology for MBP testing of proposed gel was developed and justified considering criteria given in State Pharmacopoeia of Ukraine 2.0. Originality of MPT methodology consists in the gel's antimicrobial action neutralization to decrease possible risks of false results occurrence (including microorganisms inhibited by antimicrobial action of the gel). The applicability of the methodology was determined comparing the number of test cultures CFUs in presence of gel under specified condition with number of CFUs in positive control. The methodology is suitable for microbiological purity testing of the sample, as well as for the Preservatives Efficacy Testing (PET). When applying the developed methodology, the antimicrobial action of the sample is completely eliminated. While developing the MPT methodology compliance with following acceptance criteria was confirmed for tested sample: Absence of Staphylococcus aureus (in 1 g); Absence of Pseudomonas aeruginosa (in 1 g); Total aerobic microbial count (TAMC) - 10² CFU per 1 g; Total combined yeasts and molds count (TYMC) - 10¹ CFU per 1 g. All the tested samples met the requirements of the 2.0. version of State Pharmacopoeia of Ukraine for non-sterile dosage forms for oromucosal and dermal use.